Forensic Accounting and Intelligence Gathering Approaches on The Management of Terrorist Financing in Nigeria - Aruwaji Akinola Mkchael; Olatunji Toyin Emmanuel (JAFFA, 2019)
The management of terrorism financing involves the ability to achieve control over the source, cash flow and destination of terrorists. This study examined the effects of forensic accounting and the radians of intelligence gathering approaches in the investigation of terrorist financing in Nigeria. The data for this study were sourced through primary and secondary sources. Econometrics (Factor analysis with PCA and Pearson Correlation) were used for the analyses at 0.05 level of significant. The results purview that forensic accounting approaches and intelligence gathering tool are significant in investigating the source, pathway, destination and the utilization of the resources of terrorists. It was concluded that Nigeria government should establish response to terrorism/ terror financing under the presidency to manage the problem of terror financing.